The chemistry of textile fibres - Mather, R. R. (Royal Society of Chemistry, 2011)
Discussing the chemistry of textile fibres aimed at A level students and first year undergraduates, this title explains the characteristics required for polymers to be fibre-forming, the general physical properties needed from textile fibres, and the chemistry of important natural and synthetic fibres.